Evaluating the effect of Clostridium difficile conditioned medium on fecal microbiota community structure. Issue 1 (December 2017) - Horvat, Sabina; Mahnic, Aleksander; Breskvar, Martin; Dzeroski, Saso; Rupnik, Maja
Abstract Clostridium difficile infection (CDI) is typically associated with disturbed gut microbiota and changes related to decreased colonization resistance againstC. difficile are well described. However, nothing is known about possible effects ofC. difficile on gut microbiota restoration during or after CDI. In this study, we have mimicked such a situation by usingC. difficile conditioned medium of six differentC. difficile strains belonging to PCR ribotypes 027 and 014/020 for cultivation of fecal microbiota. A marked decrease of microbial diversity was observed in conditioned medium of both tested ribotypes. The majority of differences occurred within the phylumFirmicutes, with a general decrease of gut commensals with putative protective functions (i.e.Lactobacillus, Clostridium_XIVa ) and an increase in opportunistic pathogens (i.e.Enterococcus ). Bacterial populations in conditioned medium differed between the twoC. difficile ribotypes, 027 and 014/020 and are likely associated with nutrient availability. Fecal microbiota cultivated in medium conditioned byE. coli, Salmonella Enteritidis orStaphylococcus epidermidis grouped together and was clearly different from microbiota cultivated inC. difficile conditioned medium suggesting thatC. difficile effects are specific. Our results show that the changes observed in microbiota of CDI patients are partially directly influenced byC. difficile .